Caffeine supplementation has no effect over performance in young elite football players - Mackay, K.; Diaz-Castro, F.; Penailillo, L.; Zbinden-Foncea, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Caffeine has been used as an ergogenic aid in sports performance for at least two decades (Tarnopolsky et al 2010). Studies have hypothesized that due to its stimulant properties on the central nervous system it can be used as an enhancing aid which may improve athletic performance and decrease muscle fatigue. The aim of this study was to observe the effect of the consumption of caffeine on performance in young elite football players before, throughout a 45 min match and after, simulating the end of the first half of a match and observe their performance status for the second half. Methods: In a randomized single-blind design, the players (16.4 ± 0.5 years, 69.1 ± 7.5 kg, 175.6 ± 6.6 cm, 13.7% ± 3.0 % body fat) recruited from the national junior chilean team, were given either a capsule of 3 mg · kg1 b.w. of caffeine or placebo (dextrose) 60 min prior to the match. Match activities was assessed with a GPS system and 5 m (acceleration), 15 m (flying time), and 20 m (maximal velocity) sprints and an agility test was measured with timing gates and photocells before and 5 minutes after the 45 min match. Heart rate was monitored throughout the 45 min game. Results: No differences (P >0.05) was observed between the caffeine and placebo group regarding total distance covered (4850.6 ± 231 vs. 4976 ± 386.4 m), sprint number (143.2 ± 10.8 vs. 161.4 ± 22.0), repeated sprints (143.2 ± 11.1 vs. 153.9 ± 24.1), maximal heart rate (198.9 ± 6.7 vs. 197.6 ± 8.0), high intensity zones (zone 5 and 6: 280.5 ± 34.5 vs. 237.6 ± 60.5 m and 178.7 ± 65.6 vs. 157.6 ± 59.1 m, respectively). Acceleration, flying time, maximal velocity, and the agility test showed no differences between groups, before or after the match (P >0.05). Discussion: Caffeine administration did not show an ergogenic effect in young elite football players for acceleration, flying time, velocity, agility, or any match activities. Our study is in agreement with the results observed by Pettersen et al. 2014, where no effects in performance was observed in young football players after the consumption of caffeine. Our results conclude that the consumption of 3 mg · kg1 b.w. caffeine has no effect in preserving performance after 45 min of a football match.